Dynamic modelling of alkaline self-pressurized electrolyzers: a phenomenological-based semiphysical approach - David, Martín; Alvarez, Hernán; Ocampo-Martinez, Carlos; Sánchez-Peña, Ricardo (International journal of hydrogen energy, 2020)
This paper proposes a phenomenological based semiphysical model (PBSM) for a self-pressurized alkaline electrolyzer. The model, based on mass and energy balances, represents the dynamic behaviour of hydrogen and oxygen production using electrolysis. The model allows to anticipate operational variables as dynamic responses in the concentrations of the electrolytic cell, and variations in both, level and pressure, at the gas separation chambers due to the change in electric current. The model parameters have been adjusted based on experimental measurements taken from an available prototype and through a suitable identification process. Simulation results replicate the current dynamic response of the experimental self-pressurized electrolyzer assembly. This model proves to be useful in the improvement of the control of gas production rate in this kind of assemblies, both as a validated simulation platform and as a source of reduced order models for model-based control design. [Display omitted] •A phenomenological based semiphysical model for an alkaline electrolyzer is proposed.•The model predicts dynamic variables (concentrations, pressure and level).•Model Parameters were adjusted based on experimental data via an identification method.•The model is useful for simulation and for synthesis of model-based controllers.